মহাবীৰ লাচিত আৰু শৰাইঘাট আহোম ৰাজত্বৰ সোনালী অধ্যায় - Gogoi, Anima (T. J. Gogoi, 2018)
This is historical book about Ahom dynasty. In the book, the author discusses about the Ahom kingdom under Mahaeer Lachit and Saraighat.
Mahaeer Lachit Aru Saraighat: Ahom Rajattar Xunali Adhyai
Keywords: Assamese; Assamese content; Assamese